2021
DOI: 10.9734/ijtdh/2021/v42i430447
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Deaths Occurred in Households during the Pandemic by COVID-19 in a Brazilian Amazon Region: An Epidemiological Approach

Abstract: In the absence of an analysis of deaths at home from an epidemiological perspective, this study aims to analyze and describe the epidemiological profile of deaths at home assessed by the Death Ceremony Service (DCS) during the SARS-CoV-2 pandemic in the metropolitan region of the Brazilian Amazon, Belém do Pará. A descriptive, quantitative, secondary-based study based on the databases of the Mortality Information System (SIM), referring to the deaths that occurred from March 1 to March 27 June 2020. The variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In the Brazilian Amazon, a descriptive and quantitative epidemiological study has revealed that CA is the leading cause of death (15.05%), followed by COVID-19 (10.29%) in 2020 and 2021 [6]. These statistics highlight the importance of providing emergency medical service (EMS) personnel in R&R locations with courses and training in BLS and guidance on how to instruct LP to perform cardiopulmonary resuscitation (CPR) techniques through mobile communication tools, even during a pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Brazilian Amazon, a descriptive and quantitative epidemiological study has revealed that CA is the leading cause of death (15.05%), followed by COVID-19 (10.29%) in 2020 and 2021 [6]. These statistics highlight the importance of providing emergency medical service (EMS) personnel in R&R locations with courses and training in BLS and guidance on how to instruct LP to perform cardiopulmonary resuscitation (CPR) techniques through mobile communication tools, even during a pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…However, teaching HCPs and LP in R&R locations poses significant challenges, particularly in areas such as the north of Canada and the Brazilian Amazon, where HCPs require continuous training and work in remote areas with limited resources, power, and internet access [8]. The Brazilian Amazon presents a unique challenge, as HCPs in the heart of the forest have limited access to resources [6]. One potential solution is the use of a remote online learning management system (LMS), which provides administration, documentation, tracking, reporting, automation, and delivery of educational courses and training programs [9].…”
Section: Introductionmentioning
confidence: 99%
“…In public places and outside hospitals, the global incidence of CA is reported to be 47.3 per 100,000 person-years in North America, 40.6 in Europe, 51.1 in Australia, and 45.9 in Asia [2][3][4][5]. Finally, in the Brazilian Amazon specifically, a descriptive and quantitative epidemiological study shows that CA is also the main cause when death occurs far from a hospital (15.05%), followed by COVID-19 (10.29%), even during the pandemic in 2020 and 2021 [6].…”
Section: Introductionmentioning
confidence: 99%
“…People were also in fear of seeking hospital services and being infected, and outpatient follow-up in cases of heart failure and other pathologies were interrupted. The consequences were excess deaths in people with CVD [18][19][20].…”
Section: Introductionmentioning
confidence: 99%